2013
DOI: 10.3233/jad-121819
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Co-Morbidities, and Medication Use of Patients with Alzheimer's Disease or Vascular Dementia in the UK

Abstract: Epidemiologic studies on age-specific incidence rates (IRs) separating Alzheimer's disease (AD) and vascular dementia (VaD) in the UK are scarce. We sought to assess IRs of AD and VaD in the UK and to compare co-morbidities and medication use between patients with AD, VaD, or without dementia. We identified cases aged ≥65 years with an incident diagnosis of AD or VaD between 1998 and 2008 using the General Practice Research Database (GPRD). We assessed IRs, stratified by age and gender, matched one dementia-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 29 publications
8
64
0
Order By: Relevance
“…The incidence rates (IRs) of AD per 1000 person-years in our cohort according to age categories <75 years and 75–90 years were 0.6 and 4.0 cases among men and 1.2 and 4.8 cases among women, respectively. These rates were comparable with previous estimates from the GPRD database24 and other population-based studies 25…”
Section: Methodssupporting
confidence: 91%
“…The incidence rates (IRs) of AD per 1000 person-years in our cohort according to age categories <75 years and 75–90 years were 0.6 and 4.0 cases among men and 1.2 and 4.8 cases among women, respectively. These rates were comparable with previous estimates from the GPRD database24 and other population-based studies 25…”
Section: Methodssupporting
confidence: 91%
“…AD patients used to be considered as the healthiest group of dementia patients [29], since it has been reported that AD is associated with fewer comorbidities compared with the other dementia subtypes [30,31]. These results are not in line with more recent papers that have reported the opposite [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…First, we cannot rule out the possibility of some AD and VaD case misclassification as not all dementia diagnoses can be accurately assigned by subtype. However, to reduce the possibility of misclassification when classifying AD or VaD cases, we applied a published validated algorithm [23]. Second, we were not able to control for certain potential confounders, such as level of education, marital status, or socioeconomic status, since these factors are not routinely recorded in the CPRD.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Patients with less than 3 years of active history in the database prior to the diagnosis date were excluded, as were those with a diagnosis of HIV/AIDS, alcoholism, drug abuse, multiple sclerosis, motor neuron disease, or Down's syndrome. To increase the probability of including only well-defined AD or VaD cases, a validated algorithm was applied, described in detail elsewhere [23]. In brief, this algorithm was based on recordings of specific dementia tests [e.g.…”
Section: Case Identification and Validationmentioning
confidence: 99%